THE REALITY OF FISCAL POLICY AND MEASURING ITS MONETARY EFFECTS IN THE IRAQI ECONOMY DURING THE PERIOD 2003 - 2020 (World Bulletin of Management and Law, 2022)
Involve Politics Finance on me Type From mixing and entanglement with Politics cash which affected in Economy Iraqi , The economy Iraqi suffered Much From goofs and stumbles that I worked on me obstructed offer it Economic Especially During Duration temporal confined between (2003 .) - 2020) , and upon it the politics Finance and planning and guidance , and organization Prepare From things the basic that stress in the affirmative and robbery in success recovery Economic in Iraq , and upon it so search sheds the light on me reality Politics Finance and its effects cash in Economy Iraqi.